APPLYING THE CONCEPT OF DECENT WORK TO CAMBODIA’S TEXTILE INDUSTRY: THE ILO’S ROLE IN ENSURING STATE COMPLIANCE TO INTERNATIONAL LABOR LAW - Alves, Danilo Barbosa Garrido (Revista dos Estudantes de Direito da Universidade de Brasília, 2016)
The objective of this paper is to give an overview on the situation of workers in the textile industry of Cambodia. These persons, young girls and women in their majority, deal not only with very low salaries and extremely demanding journeys, but also sexual harassment, unlawful firings of pregnant women, forced overtime and unattainable production targets, among others. What can be done by the international community (encompassing States, International Organizations, NGOs and multinationals alike) to tackle these issues, and to ensure that the decent work standards put forth by the International Labor Organization are respected in Cambodia’s garment factories? The answer to this question is multifaceted, but certainly involves cooperation between different actors - and, most importantly, actual interest in improving the working conditions of these women, something that has arguably been lacking from the analyzed actor’s side.